Genetics and genomics of pulmonary arterial hypertension - Soubrier, Florent; Chung, Wendy K.; Machado, Rajiv; Grünig, Ekkehard; Aldred, Micheala; Geraci, Mark; Loyd, James E.; Elliott, C. Gregory; Trembath, Richard C.; Newman, John H.; Humbert, Marc (The American journal of cardiology, 2013)
Major discoveries have been obtained within the last decade in the field of hereditary predisposition to pulmonary arterial hypertension (PAH). Among them, the identification of bone morphogenetic protein receptor type 2 (BMPR2) as the major predisposing gene and activin A receptor type II-like kinase-1 (ACVRL1, also known as ALK1) as the major gene when PAH is associated with hereditary hemorrhagic telangiectasia. The mutation detection rate for the known genes is approximately 75% in familial PAH, but the mutation shortfall remains unexplained even after careful molecular investigation of these genes. To identify additional genetic variants predisposing to PAH, investigators harnessed the power of next-generation sequencing to successfully identify additional genes that will be described in this report. Furthermore, common genetic predisposing factors for PAH can be identified by genome-wide association studies and are detailed in this paper. The careful study of families and routine genetic diagnosis facilitated natural history studies based on large registries of PAH patients to be set up in different countries. These longitudinal or cross-sectional studies permitted the clinical characterization of PAH in mutation carriers to be accurately described. The availability of molecular genetic diagnosis has opened up a new field for patient care, including genetic counseling for a severe disease, taking into account that the major predisposing gene has a highly variable penetrance between families. Molecular information can be drawn from the genomic study of affected tissues in PAH, in particular, pulmonary vascular tissues and cells, to gain insight into the mechanisms leading to the development of the disease. High-throughput genomic techniques, on the basis of next-generation sequencing, now allow the accurate quantification and analysis of ribonucleic acid, species, including micro-ribonucleic acids, and allow for a genome-wide investigation of epigenetic or regulatory mechanisms, which include deoxyribonucleic acid methylation, histone methylation, and acetylation, or transcription factor binding.
Available online 16 December 2013
Gesehen am 14.02.2022